Bridging hollow carbon nanostructures to hierarchically pomegranate-like microspheres for efficient oil adsorption and catalysis applications. (5th January 2023) - Tian, Danping; Li, Miao; Hao, Xiaoting; Hao, Yajuan; Zhang, Xiaoming; Yang, Hengquan
Abstract: Hierarchical carbon superstructures that built from primary nanoscale objects and featured with a micro- or macroscopic architecture are highly desired, as credited by the synergistically integrated specialties. Here, we present a simple "microconfined-assembly-locking" approach to achieve pomegranate-like mesoporous carbon microspheres (PMCMs), in which the Pickering droplet-confined colloidal particle assembly and surfactant-directed interfacial locking are coupled. The formed PMCMs possess a unique micro-nano-hierarchical structure that consisting numerous mesoporous hollow carbon nanospheres within a permeable crust. Benefitting from this hierarchical arrangement, such a peculiar architecture not only preserves high surface area, large pore volume and good accessibility of the nano-building blocks, but also upgrades in mechanical strength and easy handling ability. In addition, this strategy allows the interior microstructures to be manipulated through combinatorial varying the assembled colloidal particles and interfacial chemical locking processes. Notably, the PMCMs show superior sorption capacity and cyclability for organics or oils from water in a fixed-bed system, which could also be applied to enhance the catalytic performance in hydrogenation of aromatic compounds after loading with Ru nanoparticles. This synthetic method provides a powerful bridge between nanoscale objects and microscale patterning, and paves a way to access other novel superstructures for expanding their potential applications. Graphical abstract: Image 1